The potential mechanism of action of gut flora and bile acids through the TGR5/TRPV1 signaling pathway in diabetic peripheral neuropathic pain - Chen, Peng; Jiang, Xian; Fu, Jia; Ou, Cehua; Li, Yao; Jia, Jing; Liao, Changli (Frontiers in Endocrinology, 2024)
Diabetic peripheral neuropathic pain (DPNP) is a major complication of diabetes that markedly affects the quality of life and health status of patients. Recent studies have investigated the potential regulatory influence of gut flora and bile acids on DPNP via the TGR5/TRPV1 signaling pathway. Dysbiosis of the gut flora not only directly affects bile acid metabolism but also significantly correlates with diabetes-associated neuropathy through interactions with the bile acid receptor TGR5 and the ion channel TRPV1. This review describes how alterations in the gut flora and bile acid metabolism contribute to the pathogenesis of DPNP through the TGR5/TRPV1 signaling pathway, revealing potential applications for this pathway in DPNP management. Furthermore, experimental and clinical studies have demonstrated the modulation of gut flora and bile acid metabolism as well as targeting the TGR5/TRPV1 signaling pathway as an innovative therapeutic approach. Further studies are warranted to elucidate the underlying mechanism and develop treatment modalities based on gut flora regulation and signaling pathway interventions, thus providing novel insights and approaches for DPNP therapy.